2007
DOI: 10.1111/j.1745-7254.2007.00622.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficient growth inhibition of ErbB2-overexpressing tumor cells by anti-ErbB2 ScFv-Fc-IL-2 fusion protein in vitro and in vivo

Abstract: Aim: To investigate the antitumor activities of an anti-ErbB2 scFv-Fc-interleukin 2 (IL-2) fusion protein (HFI) in vitro and in vivo. Methods: Fusion protein HFI was constructed. The efficacy of HFI in mediating tumor cell lysis was determined by colorimetric lactate dehydrogenase release assays. The antitumor activity of HFI was evaluated in tumor xenograft models. Results: The fusion protein was folded as a homodimer formed by covalently linking Fc portions and it retained ErbB2 specificity and IL-2 biologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…BALB/c athymic nude mice received subcutaneous injections of the human ovarian carcinoma cell line SKOV-3, which expresses high levels of HER2/ neu. These mice treated intravenously with the antibody-cytokine fusion protein plus human LAK cells showed a reduction of tumor growth in comparison with treatment with rIL-2 plus LAK cells [74]. These results demonstrate the antitumor activity of this antibodycytokine fusion protein in xenograft models.…”
Section: Antibody-(il-2) Fusion Proteinssupporting
confidence: 55%
See 1 more Smart Citation
“…BALB/c athymic nude mice received subcutaneous injections of the human ovarian carcinoma cell line SKOV-3, which expresses high levels of HER2/ neu. These mice treated intravenously with the antibody-cytokine fusion protein plus human LAK cells showed a reduction of tumor growth in comparison with treatment with rIL-2 plus LAK cells [74]. These results demonstrate the antitumor activity of this antibodycytokine fusion protein in xenograft models.…”
Section: Antibody-(il-2) Fusion Proteinssupporting
confidence: 55%
“…This antibody-cytokine fusion protein retained antigen binding, and retained the biological activity of the cytokine, which was evaluated by the induction of proliferation of CTLL-2 T-cell line [73]. Recent studies have shown that anti-erbB2 scFv-Fc-(IL-2) improved the ability of IL-2 to mediate ADCC activity in vitro [74]. BALB/c athymic nude mice received subcutaneous injections of the human ovarian carcinoma cell line SKOV-3, which expresses high levels of HER2/ neu.…”
Section: Antibody-(il-2) Fusion Proteinsmentioning
confidence: 99%
“…This CD86(111)-IgG-scFv(FRP5) molecule is able to bind two ErbB2 targets on tumor cells and two CD28 proteins on T cells, providing a strong costimulatory signal in addition to mediating T cell-target interaction [170]. Along similar principles, Shi et al [171] have recently reported about an anti-ErbB2 scFv-Fc-IL2 fusion protein that was shown to mediate ADCC in vitro, and exhibited significant antitumor activity in vivo.…”
Section: Other Erbb2 Specific Antibodies and Antibody Derivativesmentioning
confidence: 91%
“…When the signals of HER2 were blocked on the surface of the HER2 overexpression cells, the growth of cells was inhibited or the cells entered apoptosis. The three types of cells including SKBR3 cells (HER2 +++ ), SKOV3 cells (HER2 ++ ) and MCF7 cells (HER2 ± ) were provided by Professor N. Guo (Institute of Basic Medical Sciences, China), and were chosen to evaluate HFI antitumor activity in vitro (33). Firstly, the cells were placed on 96-well cell plates, then, serial dilution of the samples were added to the plates and incubated at 37˚C in a humidified atmosphere of 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%